Investigating the technological pedagogical content knowledge (TPACK) skill among arabic school trainee teachers in online assessment during COVID-19 pandemic - Sahrir, Muhammad Sabri; Abd Hamid, Mohd Azrul Azlen; Zaini, Abdul Razif; Hamat, Zulkefli; Ismail, Taufik (Cognizance Research Associates, 2022)
TPACK (Technological Pedagogical Content Knowledge) is a crucial necessity for instructors and teachers during the teaching and learning process, particularly when using instructional technologies. The goal of this study is to learn more about the TPACK level of knowledge and skill among school trainee teachers in teaching Arabic language and conducting online teaching and assessment during the shutdown of schools in Malaysia due to COVID-19 Movement Restriction Control (MCO). The 32 final year students from the Kulliyyah of Education, International Islamic University Malaysia, were purposefully selected as trainee instructors (IIUM). They were assigned to teach practicum in several secondary schools in Selangor, Malaysia, in order to fulfil the Bachelor of Education degree's graduation requirement. Open-ended surveys on obstacles and challenges faced during the use of educational technology in teaching and online assessment of Arabic learning at home before and during MCO, platforms used, and further suggestions to strengthen the use of educational technology in implementing online assessment of Arabic learning were used to investigate the teachers' knowledge about three main components of TPACK, which include technology, content, and pedagogy, as well as open-ended surveys on obstacles and challenges faced during the use of educational technology in teaching and online assessment of Arabic learning at home before and during MCO. The findings and findings are helping to improve the trainee teachers' comprehension of their level of knowledge and skill in technology, pedagogy, and material in teaching Arabic, particularly during online instruction and assessment during the COVID-19 epidemic. The research could also help schools enhance their online learning techniques in preparation for post-COVID 19 schooling.